2013
DOI: 10.1182/blood-2012-12-475665
|View full text |Cite
|
Sign up to set email alerts
|

Endemic Burkitt lymphoma is associated with strength and diversity of Plasmodium falciparum malaria stage-specific antigen antibody response

Abstract: Key Points• eBL was positively associated with anti-HRP-II antibodies and inversely associated with anti-SE36 antibodies.• Anti-HRP-II antibodies suggest that recent malaria infection triggers the onset of eBL; anti-SE36 antibodies suggest long-term infection and immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
42
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 35 publications
0
42
1
1
Order By: Relevance
“…A cohort study conducted in the West Nile district in Uganda demonstrated elevated risk of eBL in children infected with EBV during infancy [3]. Several case-control studies have confirmed that children with high exposure to malaria, based on questionnaire and antibody measurements, have an elevated risk of eBL [4,5]. However, how these infections cause eBL is not well understood.…”
mentioning
confidence: 99%
“…A cohort study conducted in the West Nile district in Uganda demonstrated elevated risk of eBL in children infected with EBV during infancy [3]. Several case-control studies have confirmed that children with high exposure to malaria, based on questionnaire and antibody measurements, have an elevated risk of eBL [4,5]. However, how these infections cause eBL is not well understood.…”
mentioning
confidence: 99%
“…2 The ecological association between eBL and P. falciparum was shown in the 1970s, 1 but there is still limited evidence from studies examining this association at an individual level. [3][4][5][6][7][8] In 2012, the International Agency for Research on Cancer classified P. falciparum infection in holoendemic areas as "probably carcinogenic to humans." 9 A better description of eBL epidemiology is needed to enhance current understanding of the etiology of the disease.…”
mentioning
confidence: 99%
“…This form of leukemia accounts for only 1–2% of cases of childhood acute lymphoblastic leukemia. More commonly, patients with Burkitt's lymphoma present either as this child did, with a large abdominal mass and abdominal pain and distention, or with intussusception of the small bowel related to lymphoma involving the terminal ileum [5].…”
Section: Discussionmentioning
confidence: 94%
“…Burkitt's lymphoma is highly curable [5] and the majority of children with the disease are cured with relatively short courses of systemic multiagent chemotherapy. A risk-adapted treatment strategy is important in planning the intensity and duration of treatment for patients with Burkitt's lymphoma.…”
Section: Discussionmentioning
confidence: 99%